Risk Factors for Necrotizing Enterocolitis in Infants With Patent Arterial Duct. A Retrospective Matched Paired Analysis - Haefeli, Stephanie; Kordasz, Marcin; Tsai, Catherine; Hau, Eva-Maria; Klimek, Peter; Cholewa, Dietmar; Pavlovic, Mladen; Berger, Steffen; Kessler, Ulf (Frontiers in Pediatrics, 2020)
The development of necrotizing enterocolitis (NEC) in neonates with patent ductus arteriosus (PDA) is not well understood. Our aim was to find risk factors for NEC in children with a significant PDA and to assess differences in mortality and duration of hospital stay between patients with PDA and those with PDA and NEC. We performed a retrospective single center case control study including infants with PDA scheduled for treatment. We compared multiple patient data between patients with PDA and those with PDA and NEC from 2004 to 2018. 2018 using 1:2 and 1:1 matching. We used 1:2 matching with 26 NEC patients (cases) and 52 PDA patients without NEC (controls) and 1:1 matching with 5 NEC patients and 5 PDA patients without NEC. NEC patients had lower Apgar score (1’), more congenital malformations, more suspected sepsis, less hypotension, higher minimum platelet count and higher CRP-values during the week before NEC (P<0.05, respectively). The mortality was higher in NEC cases [29% (9/31)] compared to the control patients [2% (1/57), P<0.001]. Lower Apgar score (1â€™) was correlated with an increased risk of NEC stage III. Hypotension was inversely correlated with the odds of NEC (OR 0.3). NEC increased mortality in infants with PDA. Hypotension did not increase the risk of NEC in infants with PDA. Routine clinical parameters were not able to predict NEC in infants who suffer from PDA.